2019
DOI: 10.1017/s0140525x19001183
|View full text |Cite
|
Sign up to set email alerts
|

Psychological origins of the Industrial Revolution: More work is needed!

Abstract: I am grateful to have received so many stimulating commentaries from interested colleagues regarding the psychological origins of the Industrial Revolution and the role of evolutionary theory in understanding historical phenomena. Commentators criticized, extended, and explored the implications of the perspective I presented, and I wholeheartedly agree with many commentaries that more work is needed. In this response, I thus focus on what is needed to further test the psychological origins of the Industrial Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…Overall, our results support the hypothesis of a global historical trend toward increasing prosociality (51,52) and support the view that democratizing revolutions may be the product of a broader shift away from authoritarian preferences and toward more democratic preferences (8,9). Furthermore, our results are consistent with the hypothesis that rising living standards might contribute to the shift of psychological orientations toward cooperation (4,15,16). Note that such shifts may not only have caused political revolutions, but may also be responsible for less spectacular and more gradual institutional changes during the 17th and 18th centuries, such as increasing popular control over the monarchy, the abandonment of censorship and extrajudicial procedures, and the end of slavery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, our results support the hypothesis of a global historical trend toward increasing prosociality (51,52) and support the view that democratizing revolutions may be the product of a broader shift away from authoritarian preferences and toward more democratic preferences (8,9). Furthermore, our results are consistent with the hypothesis that rising living standards might contribute to the shift of psychological orientations toward cooperation (4,15,16). Note that such shifts may not only have caused political revolutions, but may also be responsible for less spectacular and more gradual institutional changes during the 17th and 18th centuries, such as increasing popular control over the monarchy, the abandonment of censorship and extrajudicial procedures, and the end of slavery.…”
Section: Discussionsupporting
confidence: 89%
“…The interplay between economics and cultural change is also unclear. On the one hand, democracy is more common in wealthier and better educated countries (11)(12)(13)(14), and rising living standards are thought to shift psychological orientations and preferences toward cooperation (4,15,16). In industrialized countries, higher socioeconomic status is linked to higher level of trust and lower level of authoritarianism (17,18).…”
mentioning
confidence: 99%
“…Recent work in behavioural sciences have found that resource abundance triggers cognitive exploration, curiosity, independentand open-mindedness, whereas resource scarcity triggers conservatism and conformism, in order not to take the risk of an unfruitful exploration (Dubourg et al, 2021;Dubourg & Baumard, 2022;Jacquet et al, 2018;Nettle, 2018). This interpretation fits well with the fact that at the time of the Scientific Revolution, north-western European had a very specific psychology that was more futureoriented, with higher levels of social trust, lower levels of interpersonal violence, a greater interest in romantic love and a greater interest in parental investment (Baumard, 2018).…”
Section: Discussion: the Cultural Evolution Of Sciencementioning
confidence: 53%
“…In contrast, in a resource-rich environment, individuals are futureoriented, more exploratory and more open-minded because they have more resources to cope with the inherent costs of exploration and learning (Haushofer & Fehr, 2014;Jacquet et al, 2019;Pepper & Nettle, 2017). Since science relies heavily on exploration, this predicts that a higher level of resources should be associated with a higher level of scientific creativity (Baumard, 2018). This prediction contrasts with a common assumption in cultural evolution according to which population size is crucial in explaining creativity (Collard et al, 2013;Henrich, 2004;Kremer, 1993;Shennan, 2001).…”
mentioning
confidence: 93%
“…Finally, one simple explanation of the British advantage in skilled labour derived from the higher overall quality of the British labour force compared to the Continent, in large part because of the relatively high living standards and good nutrition enjoyed by the British population on the eve of the Industrial Revolution. British workers were taller and by most accounts stronger than Continental ones (Kelly et al 2014, Baumard 2019). As Nicolas Baumard points out, a workforce that did not grow up in grinding poverty would be more likely to take risks, be more resourceful and cooperative, and more likely to show initiative.…”
Section: The Roots Of British Technological Competencementioning
confidence: 99%